Developing Mobile Website-Based Learning Media for Students to Learn Speaking in English - Masduqi, Harits; Pratama , Chyntia Wahyu; MR, Elvira Rosyida (Department of English Language Education, UIN Sunan Ampel Surabaya, 2024)
This study is intended to create simple mobile website-based learning media to facilitate the students to learn speaking skills in English. The study used Borg and Gall’s development model with six steps of modified procedures, including research and information collection, planning, developing, design validation, design revision, and implementation. The researchers carried out a product feasibility test through the product validation and product trials on the field research. The product validation was realised by submitting a questionnaire to the media expert and learning material experts, while the product trials were conducted by distributing the user feedback questionnaire to the students. The results showed that the feasibility testing score by the media expert was 88% and the product validation score by the material experts was 87%, meaning that the mobile website-based learning media was feasible to use. Furthermore, based on the user feedback questionnaire results, the cumulative percentage was 87,50% which supports the product validity. Thus, it can be said that the mobile website-based learning media is feasible and valid to use for learning speaking in English.